“Vocês fazem isso porque tem medo de nos ouvir”: análise dos discursos do estado quanto aos direitos indígenas diante da Usina Belo Monte - Lacerda, Lidia Neira Alves (2017)
This dissertation presents a description and analysis of the state actions related to Civil Public Action n. 20063903000711-8, judged by Brazilian Federal Prosecution Service (MPF), concerning Belo Monte plant construction. It focuses on the controversy arising the absence of previous consultations or hearings, as determined by Convention n. 169 and Brazilian Federal Constitution of 1988. Using the concepts of governmentality and commensurability, this study intends to analyse discursive representation and state matters which were used to make possible the construction of Belo Monte plant, even in disagreement with what is found in the current indigenous law. As a result of this, we also look into the interpretation of legal mechanisms, which prevented indigenous people participation, and their effective citizenship and authonomy, in opposite to a multiethnic state.